Financial Literacy dan Financial Technology Serta Pengaruhnya Terhadap Keputusan Berinvestasi di Reksa Dana Melalui Aplikasi Bibit Pada Generasi Z: Financial Literacy and Financial Technology and Their Influence on Investment Decisions in Reksadana the Bibit Application Among Generation Z - Aisa Rahma; Nurvi Oktiani; Syahrir (Jurnal Ilmiah Produktif, 2025)
Bibit is an investment fund application designed to help beginners start investing. This application allows users to start investing optimally according to their desired level of risk without requiring any prior experience. This study is helpful for examining how financial technology and financial knowledge affect mutual fund investing choices made via the Bibit app among generation z. The research method used involves quantitative primary data, using a questionnaire provided through Google Forms, and 150 respondents were selected using the Hair formula. Purposive sampling was used to sampling methode for this study., and SPSS version 22 was utilised to analyse the data. There are multiple testing phases in the data analysis process, including hypothesis testing, Coefficient of determination testing, linear regression testing, and conventional assumptions. The findings of this investigation demonstrate that they both strongly and favourably affect investment choices.